Pengembangan E-Modul Menggunakan Flipbook Maker Berbasis Metode Problem Solving untuk Meningkatkan Keterampilan Bernalar Kritis Siswa Kelas V Sekolah Dasar - Nadiman, Nadiman; Purnamasari, Iin; Sumarno, Sumarno (Universitas PGRI Semarang, 2023)
This study aims to determine the feasibility, practicality, and effectiveness of e-module teaching materials using problem solving learning model-based flipbook makers. This research is research and development by adopting the Brog & Gall model (containing potential and problem analysis, product design, product assessment, product manufacture, product testing, and final product manufacture.). The analysis stage of potential problems includes carrying out initial observations during pre-research analyzing problems, media, teachers, and students. The product design stage includes instructions for use, table of contents, mapping of Basic Competency, glossary, indicators and learning objectives, benefits of e-modules, maps concepts, materials, summaries, exercises, worksheets, competency tests, answer keys and bibliography. The development stage is making e-module teaching materials with product aspects, material content, validation and display of the production of e-module teaching materials using a flipbook maker and also developing data instruments. The data collection instruments in this study were product feasibility from expert lecturers and education practitioners, practical worksheets for elementary school teachers and peers. For students readability sheets, pretest and posttest questions for the final evaluation of student learning after using the e-module. The data collection instrument was based on assessments by experts/lecturers, education practitioners, class teachers, peers and also students as research objects. The implementation stage of using the e-module has been developed for fifth grade students at SDN Karangasem 08 Batang. The trials carried out at this stage were product feasibility tests, product legibility and pretest posttest for students, with the results showing an increase in students' critical thinking after students used e-modules using flipbook makers. Evidenced by the paired t-test, the magnitude of the increase in the average pretest and posttest scores shows that there is an average increase (gain) in the pretest and posttest values obtained by 61.00 and 77.72 with an average difference of 16.72. The increase in average indicates that the E-module Flipbook based on the problem solving learning model is effectively used in social studies content in class V SDN Karangasem 08 Batang. The evaluation stage includes the form of evaluation carried out at each stage of the Borg and Gall model. The data analysis technique used is the manova and n-gain tests. The results show that the developed flipbook maker-based e-module is suitable for use in Civics learning. The e-module is feasible and practical to use, and effective for improving the critical thinking skills of fifth grade elementary school students.